Physics matters : - Trefil, James S. (John Wiley & Sons, 2004)
From amusement park rides to critical environmental issues such as energy generation-physics affects almost every aspect of our world. In PHYSICS MATTERS, James Trefil and Robert Hazen examine the fundamental physics principles at work behind the many practical applications that fuel our society and individual lives. Their goal is to promote a deeper understanding of how the great ideas of physics connect to form a much larger understanding of the universe in which we live.